非無菌製剤の製造環境管理に関する研究 ―リスクに基づく維持/管理手法の構築 - 光吉, 浩; 那須川, 真澄; 井上, 敬介; 山中, 邦昭; 杉山, 篤央; 堀江, 匠; 須藤, 眞生; 白井, 俊光; 浦山, 由巳; 村上, 大吉郎; 田原, 繁広; 三原, 宏美; et al. (PDA Journal of GMP and Validation in Japan, 2015)
This publication has been prepared to express a sound and practical view on the better manufacturing environmental control for non-sterile pharmaceutical dosage forms, which has been discussed for several years by a special working group members of Kansai Study Group (KSG) accredited as one of the committees in Parenteral Drug Association (PDA) Japan Chapter. The opinions proposed or advanced in the document are formed for the purpose of furnishing a beneficial and valuable guide with advisability to any persons or organizations concerned in establishing appropriate manufacturing control systems for quality products.   The leading topics discussed among the WG are focused on the prevention against cross-contamination and foreign matter ingress, and categorized into five subjects composed of HVAC systems, premises, gowning, cleaning, and cleanliness standards. Constructive and earnest discussion therein has been devoted to the key processes, wherein considerable amounts of powders are handled for the successful operations of weighing, granulation, mixing, and tableting. In the expectation of good usage, many of the principles and the way of thinking presented hereupon, in particular can be applied or rearranged to a wide spectrum of other manufacturing processes for various dosage forms of non-sterile drug products.